2022
DOI: 10.1002/pc.26902
|View full text |Cite
|
Sign up to set email alerts
|

Use of synthetic wollastonite nanofibers in enhancing mechanical, thermal, and flammability properties of polyoxymethylene nanocomposites

Abstract: This study investigates the mechanical, thermal, and flammability properties of synthetic wollastonite nanofibers (SWN) reinforced polyoxymethylene (POM) nanocomposites. SWN has been added into the POM nanocomposites in the range of 0.5-3 phr via melt blending. The mechanical properties were investigated through tensile and impact tests with scanning electron microscopy and energy dispersive X-ray analysis. The thermal characterization was performed by thermogravimetry analysis and differential scanning calori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 75 publications
1
8
0
Order By: Relevance
“…As previously reported in our study, it was anticipated that SWN did not perform as a nucleating agent for POM nanocomposites, which is in line with our expectations. 30 Furthermore, the aspect ratio of SWN did not significantly affect the X c of POM nanocomposites based on the result tabulated in Table 3. It is suggested that the decrement in the X c of POM nanocomposites caused by the incorporation of SWN 30 has overshadowed the effect of the SWN aspect ratio.…”
Section: Melting and Crystallizing Behaviormentioning
confidence: 87%
See 3 more Smart Citations
“…As previously reported in our study, it was anticipated that SWN did not perform as a nucleating agent for POM nanocomposites, which is in line with our expectations. 30 Furthermore, the aspect ratio of SWN did not significantly affect the X c of POM nanocomposites based on the result tabulated in Table 3. It is suggested that the decrement in the X c of POM nanocomposites caused by the incorporation of SWN 30 has overshadowed the effect of the SWN aspect ratio.…”
Section: Melting and Crystallizing Behaviormentioning
confidence: 87%
“…Then, SWN was incorporated into the POM matrix with the optimum filler content of 1 phr that provided the best-balanced properties of POM/SWN nanocomposites. 30 POM/SWN nanocomposites were prepared by a two-stage melt blending for better filler dispersion in the POM. During the melt blending, a single screw extruder (model: HAAKE Poly-Lab OS) was used with a barrel temperature of 190 C and screw rotation of 60 rpm.…”
Section: Preparation Of Pom Nanocompositesmentioning
confidence: 99%
See 2 more Smart Citations
“…With the recent focus on nanotechnologies, nanoscale wollastonite has been incorporated into polymers to form polymer nanocomposites with enhanced functional properties. [17][18][19] Nano-scale wollastonite with tunable shapes and sizes can be obtained through chemical routes. 20 Luyt and coworkers synthesized wollastonite nanoparticles through a sol-gel reaction route.…”
Section: Introductionmentioning
confidence: 99%